2020
DOI: 10.1002/ajb2.1499
|View full text |Cite
|
Sign up to set email alerts
|

Pollination effectiveness of specialist and opportunistic nectar feeders influenced by invasive alien ants in the Seychelles

Abstract: PREMISE: Opportunistic nectar-feeders may act as effective pollinators; nonetheless, we still lack information on whether these opportunistic species differ in their pollination effectiveness from specialized nectarivorous vertebrates and insects. Many nectar specialists have coevolved with the plants on which they feed; therefore, we would expect higher pollination effectiveness in specialists than in opportunistic feeders. Here, we assessed quantity and quality components of pollination effectiveness in spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The distribution of pollinator taxonomic orders across latitudes, islands and mainlands in this study generally fits the natural distribution revealed by previous studies, for example, dipterans dominate high latitudes while hymenopterans, especially bees, are more common towards low latitudes (Devoto et al., 2005; Elberling & Olesen, 1999), and more lizard pollinators and ‘other’ pollinators (can be viewed as opportunistic pollinators) occur on islands than mainlands (Fuster et al., 2020; Hervías‐Parejo & Traveset, 2018; Olesen & Valido, 2003; Wang et al., 2020). The lack of mammal pollinators such as bats (Fægri & van der Pijl, 1979), and the relative rarity of bird pollinators especially in temperate regions (Zanata et al., 2017), are taxonomic biases in our dataset and in other global analyses of pollination networks (Olesen & Jordano, 2002; Traveset et al., 2016; Trøjelsgaard & Olesen, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The distribution of pollinator taxonomic orders across latitudes, islands and mainlands in this study generally fits the natural distribution revealed by previous studies, for example, dipterans dominate high latitudes while hymenopterans, especially bees, are more common towards low latitudes (Devoto et al., 2005; Elberling & Olesen, 1999), and more lizard pollinators and ‘other’ pollinators (can be viewed as opportunistic pollinators) occur on islands than mainlands (Fuster et al., 2020; Hervías‐Parejo & Traveset, 2018; Olesen & Valido, 2003; Wang et al., 2020). The lack of mammal pollinators such as bats (Fægri & van der Pijl, 1979), and the relative rarity of bird pollinators especially in temperate regions (Zanata et al., 2017), are taxonomic biases in our dataset and in other global analyses of pollination networks (Olesen & Jordano, 2002; Traveset et al., 2016; Trøjelsgaard & Olesen, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Ants, though sometimes help in pollinating owers of some species [28][29][30][31] have a complex interaction with the plants 14 . This interaction has a narrow cost-bene t border 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Horvitz & Schemske 1986; Rodriguez‐Cabal et al, 2012) and pollination (e.g. Fuster et al, 2020) and spread diseases in pollinator communities (Vanbergen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%